Synthesis and significant cytostatic activity of 7-hetaryl-7-deazaadenosines - Bourderioux, Aurelie; Naus, Petr; Perlíková, Pavla; Pohl, Radek; Pichová, Iva; Votruba, Ivan; Dzubák, Petr; Konecný, Petr; Hajdúch, Marián; Stray, Kirsten M; Wang, Ting; Ray, Adrian S; et al. (Journal of medicinal chemistry, 2011)
A series of 7-aryl- and 7-hetaryl-7-deazaadenosines was prepared by the cross-coupling reactions of unprotected or protected 7-iodo-7-deazaadenosines with (het)arylboronic acids, stannanes, or zinc halides. Nucleosides bearing 5-membered heterocycles at the position 7 exerted potent in vitro antiproliferative effects against a broad panel of hematological and solid tumor cell lines. Cell cycle analysis indicated profound inhibition of RNA synthesis and induction of apoptosis in treated cells. Intracellular conversion to triphosphates has been detected with active compounds. The triphosphate metabolites showed only a weak inhibitory effect on human RNA polymerase II, suggesting potentially other mechanisms for the inhibition of RNA synthesis and quick onset of apoptosis. Initial in vivo evaluation demonstrated an effect of 7-(2-thienyl)-7-deazaadenine ribonucleoside on the survival rate in syngeneic P388D1 mouse leukemia model.
Keywords: RNA Polymerase II; Humans; adenosinkinasa; Tubercidin; cytostatické látky; Antineoplastic Agents; lidé; zvířata; myši; Mice; apoptóza; tubercidin; RNA-polymerasa II; nádorové buněčné linie; protinádorové látky; Cytostatic Agents; Animals; Cell Line, Tumor; Adenosine Kinase; Apoptosis